A REVIEW OF RESEARCH ON COMMON BIOLOGICAL AGENTS AND THEIR IMPACT ON ENVIRONMENT - Mashiatullah, A.; Qureshi, R. M.; Qureshi, R. M. (The Nucleus, 2020)
Biological agents are unique class of microorganisms which can be used to produce the disease in large populations of humans, animals and plants. If used for hostile purposes, any disease-causing microorganism could be considered a weapon. The use of biological agents is not a new concept and history is replete with examples of biological weapon use. Before the 20th century, biological warfare took on three main forms by deliberate poisoning of food and water with infectious material, use of microorganisms or toxins in some form of weapon system, and use of biologically inoculated fabrics. Four kinds of biological warfare agents are bacteria, viruses, rickettsiae, fungi. These are distinguished by being living organisms, that reproduce within their host victims, who then become contagious with a deadly multiplier effect, bacteria, viruses, or fungi or toxin found in nature can be used to kill or injure people. Biological agents may be used for an isolated assassination, as well as to cause incapacitation or death to thousands. These biological agents represent a dangerous military threat because they are alive, and are therefore unpredictable and uncontrollable once released. The act of bioterrorism can range from a simple hoax to the actual use of biological weapons. Biological agents have the potential to make an environment more dangerous over time. If the environment is contaminated, a long-term threat to the population could be created. This paper discusses common biological agents, their mode of action in living organisms and possible impact on the environment.